2016
DOI: 10.18632/oncotarget.9257
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming of glioblastoma cells by L-asparaginase sensitizes for apoptosis in vitro and in vivo

Abstract: Cancer cells display a variety of global metabolic changes, which aside from the glycolytic pathway largely involve amino acid metabolism. To ensure aggressive growth, tumor cells highly depend on amino acids, most notably due to their pivotal need of protein synthesis. In this study, we assessed the overall hypothesis that depletion of asparagine by E. coli-derived L-asparaginase might be a novel means for the therapy of one of the most recalcitrant neoplasms and for which no efficient treatment currently exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 55 publications
2
44
0
Order By: Relevance
“…We reported in 2013 that the anti-leukemia agent E. coli-ASNase enhances chemo-cytotoxicity against brain tumors (20). Additional studies validating the antiglioblastoma activity of ASNase in vitro and in vivo were recently reported (33,34). Our current study shows that activity of Erwinaze against brain tumor cells is comparable to the reported in vitro effects of E. coli-ASNase ( Figure 1A and 4).…”
Section: Discussionsupporting
confidence: 84%
“…We reported in 2013 that the anti-leukemia agent E. coli-ASNase enhances chemo-cytotoxicity against brain tumors (20). Additional studies validating the antiglioblastoma activity of ASNase in vitro and in vivo were recently reported (33,34). Our current study shows that activity of Erwinaze against brain tumor cells is comparable to the reported in vitro effects of E. coli-ASNase ( Figure 1A and 4).…”
Section: Discussionsupporting
confidence: 84%
“…What makes this drug so interesting to be used in combination therapy against glioblastoma is the fact that L-asparaginase elicits its anti-tumor effects without the need to pass the blood brain barrier, which is an inherent concern for the drug treatment of glioblastoma. By its own, L-asparaginase was particularly active in a pediatric glioblastoma cell line, SF188, which is known to express high levels of c-myc [34]. Based on this notion, we were anticipating that L-asparaginase might have high anti-proliferative activity in stem cell-like glioma cells since those cell cultures are particularly dependent on c-myc.…”
Section: Bh3-mimetics Targeting Bcl-xl Bcl-2 and Bcl-wmentioning
confidence: 99%
“…Based on this notion, we were anticipating that L-asparaginase might have high anti-proliferative activity in stem cell-like glioma cells since those cell cultures are particularly dependent on c-myc. Unfortunately, single treatment with L-asparaginase was rather ineffective against these cells [34]. However, when combined with ABT-263, L-asparaginase showed strong synergism in relevant model systems of glioblastoma, including stem cell-like glioma cells.…”
Section: Bh3-mimetics Targeting Bcl-xl Bcl-2 and Bcl-wmentioning
confidence: 99%
See 1 more Smart Citation
“…In our recently published manuscript, we have taken advantage of this approach by utilizing L-asparaginase, which is an approved drug for acute lymphoblastic leukemia, for the treatment of glio-blastoma. While this idea has been pursued for brain tumors before, we have further refined this strategy by combining L-asparaginase with an orally available inhibitor targeting Bcl-xL [2]. In that regard, we utilized one of the recently designed BH3-mimetics, ABT-263, which aside from Bcl-xL also interferes with Bcl-2 [3].…”
mentioning
confidence: 99%